Distance learning in developing EFL students’ attitudes during post-pandemic: Effectiveness and barriers - Daulay, Sholihatul Hamidah; Dalimunte, Muhammad; Adelita, Devika (Research and Social Study Institute, 2023)
The objectives of this study were to investigate what the students thought about the effectiveness of distance learning in developing attitudes and the barriers that came after the pandemic. This research was conducted using the qualitative research method. Forty EFL students from a senior high school in Medan took part in this study, twelve statements on questionnaires with the options strongly agreed, agreed, neutral, disagreed, and strongly disagree, as well as a semi-structured interview with four students who volunteered to participate, were used to gather the data. The findings indicated that the students have a positive attitude toward the effectiveness of distance learning in ELT classrooms. Besides the effectiveness, it was found that there were some barriers to the utilization of distance learning in the case of attitudes such as students’ lack of preparation (doing other activities during learning), lack of concentration (asleep), and lack of dress etiquette (not neat).